Employers' views of the 'Healthy Hub Roadshow': a workplace HIV testing intervention in England - Blake, Holly; Hussain, Basharat; Hand, Jenny; Juma, Amdani; Evans, Catrin (Taylor & Francis, 2018)
We explored employer uptake and perceptions of workplace HIV testing delivered to employees as part of Healthy Hub Roadshow, a multi-component general health check. Intervention included health checks with tailored advice delivered to 776 employees at 20 events hosted by 11 different workplaces (29 approached, 38% employer uptake). Delivery partners were third sector organisations with significant expertise in HIV testing and support. Health checks included optional HIV test (using 4th generation Insti finger prick rapid tests), Body Mass Index (BMI), blood glucose, blood pressure, and cholesterol. Mixed-methods evaluation included post-event online survey and qualitative interviews with participating employers. Declining employers were invited to complete an online feedback survey.